1999
DOI: 10.1093/jnci/91.21.1876
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Transport in Xenopus Oocytes Expressing Recombinant Plasma Membrane Mammalian Nucleoside Transporters

Abstract: Background: Gemcitabine, a pyrimidine analogue of deoxycytidine, is an anticancer nucleoside drug that requires functional plasma membrane nucleoside transporter proteins to reach its intracellular targets and cause cytotoxicity. Because of technical difficulties inherent in studying nucleoside transport in human cells, we rigorously defined gemcitabine membrane transportability by producing each of the available human (h) and rat (r) recombinant nucleoside transporters (NTs) individually in Xenopus laevis ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
147
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(153 citation statements)
references
References 25 publications
5
147
0
1
Order By: Relevance
“…It has been shown that modulation of cellular enzymes of gemcitabine transport and metabolism influences drug activity in vitro (Mackey et al, 1998(Mackey et al, , 1999Goan et al, 1999;Ritzel et al, 2001). Cellular enzymes of gemcitabine transport and metabolism, that is, hENT1, dCK, RRM1, and RRM2, are well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that modulation of cellular enzymes of gemcitabine transport and metabolism influences drug activity in vitro (Mackey et al, 1998(Mackey et al, , 1999Goan et al, 1999;Ritzel et al, 2001). Cellular enzymes of gemcitabine transport and metabolism, that is, hENT1, dCK, RRM1, and RRM2, are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies performed on human cancer cell lines, human equilibrative nucleoside transporter-1 (hENT1) was found to be the major gemcitabine transporter (Garcia-Manteiga et al, 2003). If gemcitabine is not transported into the cell via hENT1 it cannot inhibit cell growth (Mackey et al, 1998;Rauchwerger et al, 2000), but increased hENT1 abundance facilitates efficient cellular entry of gemcitabine and confers increased cytotoxicity (Mackey et al, 1999;Ritzel et al, 2001). Inside the cell, gemcitabine is phosphorylated by deoxycytidine kinase (dCK) in a rate-limiting step.…”
mentioning
confidence: 99%
“…The latter show significantly lower affinities for substrates than CNTs and may be reversible depending on how the substrate concentration gradients change across the plasma membrane. Substrate selectivity and their pharmacological profiles, [35][36][37][40][41][42][43] still incomplete, are summarized in Table 2.…”
Section: How Nucleoside-derived Drugs Are Transported Into Cells?mentioning
confidence: 99%
“…Substrate selectivity in the CNT gene family is narrower than for ENTs. For instance, gemcitabine is a high-affinity substrate for hCNT1 but it is not recognized by hCNT2 42 and appears to be less effectively taken up by the hCNT3 isoform. 45 In contrast, hCNT3 takes up fludarabine with high affinity, while hCNT1 does not recognize it and hCNT2, although inhibited by it, does not take it up.…”
Section: Nucleoside Transporters In Cllmentioning
confidence: 99%
“…CNT1/2/3 proteins transport a broad spectrum of antiviral and anticancer nucleoside analogues (Huang et al, 1995;Yao et al, 1996b;Ritzel et al, 1997Ritzel et al, , 1998Ritzel et al, , 2001Mackey et al, 1999;unpublished observation). hCNT1 and rCNT1, for instance, transport the antiviral drugs 3 -azido-3 -deoxythymidine (AZT) and 2 3 -dideoxycytidine (ddC), but not 2 3 -dideoxyinosine (ddI).…”
mentioning
confidence: 99%